Construction contract management using value packaging systems. Issue 1 (2nd January 2017) - Safa, Mahdi; Shahi, Arash; Haas, Carl T.; Hipel, Keith W.
Abstract : In large construction projects, optimally dividing, packaging, and awarding the work amongst contractors and suppliers can be challenging. Typically, this procurement process is executed in the pre-construction phase based on the experience and judgement of the project leadership team. Once procurement is completed, it is difficult to demonstrate whether the results of this process are optimal, or to explain the rationale behind decision making. An auditable and robust method is needed to address these issues, while still taking into account the expertise of the project leadership team. Thus, a comprehensive construction value packaging system (CVPS) is presented which serves as a computational and process environment for assisting project leaders by increasing the efficiency, auditability, and effectiveness of the procurement process. The development of this system requires a new concept to be defined, the construction value unit (VU), whose scope covers value-added work defined by type of activity, its stage in the value chain, and its specifications. Construction value packages are composed of VUs. Research findings demonstrate that the VPS has the potential to improve the contract management of an enterprise-wide construction supply chain.